Gunshot liver injuries grade I–III and related liver enzyme values - Radunović, Miodrag; Vuković, Marko; Radojević, Nemanja; Lazović, Ranko; Radunović, Miroslav (Vojnosanitetski pregled, 2021)
Background/Aim. The liver is one of the most commonly injured solid organ in patients with abdominal gunshot wounds. The aim of this study was to investigate correlation between aspartate aminotransferase (AST) and alanine aminotransferase (ALT) levels as well as correlation between liver enzymes and Injury Severity Score (ISS) among patients sustained a gunshot liver injury. Methods. The study included 30 patients with a gunshot liver injury. Patients were divided into three groups, according to the American Association for the Surgery of Trauma injury grade. We included only patients with first (I), second (II) and third degree (III) injury. AST and ALT levels were also initially measured, and then consecutively each day, up to the fifth post-traumatic day, in order to determine which of them is better and more stable predictor of severity of gunshot liver injury. Results. ALT had significant positive correlation with a low-degree gunshot liver injury, on the day zero, post-traumatic day one and day two. Nevertheless, AST/ALT relation throughout post-traumatic five day period regarding an injury grade correlates best in II grade injury. At the end, strong positive correlation between ALT and ISS was observed (p < 0.05). Conclusion. Presented data clearly shows that ALT is better gunshot liver injury predictor than AST, with strong predictive value regarding injury severity, in first days after liver trauma. Therefore, it could be easily available, cheap and reliable prognostic tool for complexity of liver trauma. ALT prediction value is more significant for I and II injury, grade. Correlation between AST and ALT exists only for specific injury grade (II), but not in general.